Wybrane metody oceny wpływu innowacyjności na pozycję konkurencyjną przedsiębiorstw - Kusa, Rafał (Selected Methods of Assessment of Innovation's Influence on Competitiveness of Enterprises, 2006)
The aim of the paper is to presents methods which could be useful in assessment of innovation's influence on competitiveness of enterprises: panel of experts, regression analyses and cluster analyses. The research on travel agents' competitiveness is presented as an example of application of discussed methods.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 499-505